Gamified training: a new concept to improve individual soft skills - Ardian Adhiatma; Tina Rahayu; Olivia Fachrunnisa (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2019)
This study discusses a new concept of